2009
DOI: 10.1007/s11144-009-0103-4
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of Novozym® 435 during the esterification of ibuprofen with ethanol: evidences of the detrimental effect of the alcohol

Abstract: The stability of Novozym Ò 435 in the esterification of ibuprofen using ethanol as reactant and solvent was investigated. Additionally, the surface interaction of the isomers of ibuprofen and ethanol with the biocatalyst was screened through conventional adsorption isotherms and temperature programmed surface reaction (TPSR). These investigations evidenced strong alcohol adsorption and dissolution of the biocatalyst, which explains its deactivation upon reuses in the esterification reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 6 publications
1
18
0
1
Order By: Relevance
“…In fact, the effect of particle size has been studied in the synthesis of monobenzoate glycerol using Novozym ® 435 in the range of 0.075 and 0.65 mm, concluding that internal diffusion is important for the reaction rate of the esterification of benzoic acid with glycerol [49]. In this way, we have estimated the effectiveness factor (η) for the immobilized enzyme, proposing a system of equations for each fraction by using Equation (8), and this was confirmed with the mean fraction results obtained using Equation (9). Table 1 shows the values of the effectiveness factor calculated according to the aforementioned procedure.…”
Section: Internal Mass Transfersupporting
confidence: 72%
See 1 more Smart Citation
“…In fact, the effect of particle size has been studied in the synthesis of monobenzoate glycerol using Novozym ® 435 in the range of 0.075 and 0.65 mm, concluding that internal diffusion is important for the reaction rate of the esterification of benzoic acid with glycerol [49]. In this way, we have estimated the effectiveness factor (η) for the immobilized enzyme, proposing a system of equations for each fraction by using Equation (8), and this was confirmed with the mean fraction results obtained using Equation (9). Table 1 shows the values of the effectiveness factor calculated according to the aforementioned procedure.…”
Section: Internal Mass Transfersupporting
confidence: 72%
“…Novozym ® 435 is a commercially available heterogeneous biocatalyst Candida antarctica lipase B. This enzyme preparation has been used in the esterification of profens such as naproxen [7], ibuprofen [8,9], flurbiprofen [10], and ketoprofen [11] for the synthesis of prodrugs; it has also been used in the production of biodiesel [12][13][14] and in the development of polymerization bioprocesses [15][16][17]. It can actuate when suspended in various solvents and renewable resources such as supercritical carbon dioxide, ionic liquids [18], 2 of 19 glycerol [19][20][21], and deep eutectic solvents (DES), the high viscosity of which, as in the case of glycerol, can be reduced by water addition [22].…”
Section: Introductionmentioning
confidence: 99%
“…The denaturing effect of alcohols on proteins, causing enzyme deactivation is well known. Progressive deactivation after several reuses of the biocatalyst during the esterification was also observed [20]. In previous reports, 85% of the initial Novozym 435 activity was maintained after 9 batches in the transesterification of vegetable oils and ethanol…”
Section: Effect Of Alcoholsmentioning
confidence: 69%
“…The authors performed the enantiomeric esterification at 45 C in contrast with previous investigations in solventless media carried at 55-70 C. The authors reported a 62% conversion of racemic ibuprofen with a 50% enantioselectivity towards the S(+)-enantiomer although some drawbacks in the physical integrity of Novozym Õ 435 were demonstrated (José & Briand, 2010;José et al, 2011).…”
Section: Alcohols As Acyl Acceptors In the Kinetic Resolution Of Racementioning
confidence: 98%